Trastorno de somatización y su incidencia en la salud mental en una paciente de 30 años del cantón Babahoyo - Paredes Rosado, Dayana Lilibeth (2021)
What is reality or the right question is: what gives meaning to reality or life? The meaning of everything that surrounds us is the process or attribution of our own thoughts about the good and evil of the things that surround us, because for some what happened either events or events will be something good, and for others, it will be something negative. From the perspective of a country, moral beliefs and values will be considered as typical customs of its culture and as an appropriate style, but in another country with a different culture this would be totally inappropriate. Therefore, our consideration of our environment, such as our social relationships, the desires and goals proposed by each of us, go in the direction of the meaning we give to beliefs. However, when the ideas built to obtain or satisfy our desires are demanding and have no logical basis, they can cause the individual to enter a state of intolerance and frustration, thus creating a threatening reality in oneself, leading to a disorder.